Setting Sight on Role Playing: To Accommodate or to Repudiate? - Fata, Ika Apriani; Kasim, Usman; Juniyana, Dwi (SOSIOHUMANIKA, 2017)
ABSTRACT: Role play is the main important technique in CLT (Communicative Language Teaching), as it gives students a lot of prospects to practice communicating of various social contexts and in different social roles. To set sight on role play by means to look at EFL (English as a Foreign Language) teacherâs experience and studentsâ perspectives of role play technique enactment in teaching speaking by using qualitative design. This study provided framework for the instrument of observation sheet adapted from J. Brown (2001), field notes adapted from C. Marshall & G.B. Rossman (2006), and interview guide adapted also questionnaire from P. Islami & T. Islami (2013). The methodology designated the combination of four mountainsides to expose in-depth the urgency of role play in which applied since 1936. The result of interview exposed that the English teacher claimed that role play is a technique applied to promote speaking and it is corroborated by the result of field note. In addition, speaking of studentsâ perspective depicted that the students indeed agreed themselves of the usefulness of role play to enhance their speaking skill and motivation. Thus, students asserted that the learning is more fun and enjoyable through role play. The researchers recommended to have a deep look at reasoning studentsâ point of view in terms of role play technique implementation in non-English class. And see ascertains how beneficial, it is in terms of role play in a large classroom.KEY WORD: Perspective; English as a Foreign Language; Setting Sight; Role Playing; Communication Skill.Â RESUME: âMenata Pengamatan pada Bermain Peran: Untuk Mengakomodasi atau Mengabaikan?â. Bermain peran adalah teknik penting dan utama dalam CLT (Pembelajaran Bahasa Secara Komunikatif), karena memberi siswa banyak prospek untuk berlatih mengkomunikasikan berbagai konteks sosial dan peran sosial yang berbeda. Mengacu pada permainan peran dengan cara melihat pengalaman guru EFL (Bahasa Inggris sebagai Bahasa Asing) dan perspektif siswa tentang teknik permainan peran dalam pengajaran berbicara dengan menggunakan desain kualitatif. Studi ini memberikan kerangka kerja untuk instrumen lembar observasi yang diadaptasi dari J. Brown (2001), catatan lapangan yang diadaptasi dari C. Marshall & G.B. Rossman (2006), dan panduan wawancara yang juga mengadaptasi kuesioner dari P. Islami & T. Islami (2013). Metodologi tersebut menetapkan kombinasi empat hal penting untuk mengungkapkan secara mendalam urgensi permainan peran yang diterapkan sejak 1936. Hasil wawancara mengungkapkan mengenai guru bahasa Inggris yang mengklaim bahwa bermain peran adalah teknik yang diterapkan untuk mempromosikan pembelajaran dan ini diperkuat oleh hasil catatan lapangan. Selain itu, berbicara tentang perspektif siswa menggambarkan bahwa para siswa benar-benar menyetujui kegunaan bermain peran untuk meningkatkan kemampuan berbicara dan motivasi mereka. Dengan demikian, siswa menegaskan bahwa pembelajaran lebih menyenangkan dan menggembirakan melalui bermain peran. Para peneliti merekomendasikan untuk melihat secara mendalam penalaran tentang sudut pandang siswa dalam hal penerapan teknik bermain peran di kelas non-Inggris. Dan mengingat betapa ada manfaatnya, maka hal itu perlu dilakukan bermain peran di kelas yang lebih besar.KATA KUNCI: Perspektif; Bahasa Inggris sebagai Bahasa Asing; Menata Pengamatan; Bermain Peran; Kemampuan Berkomunikasi.Â Â Â Â About the Authors: Ika Apriani Fata, Usman Kasim, and Dwi Juniyana are the Lecturers at the Department of English Education, Faculty of Teacher Training and Education UNSYIAH (University of Syiah Kuala), Jalan Krueng Kale No.21, Banda Aceh, Nanggoe Aceh Darussalam, Indonesia. For academic interests, corresponding author is: ika.apriani@unsyiah.ac.idHow to cite this article? Fata, Ika Apriani, Usman Kasim & Dwi Juniyana. (2017). âSetting Sight on Role Playing: To Accommodate or to Repudiate?â in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.10(1) May, pp.91-106. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of the article: Accepted (April 25, 2016); Revised (October 9, 2016); and Published (May 30, 2017).